Isolation And Confirmation Of Leptospira Canicola From The Aborted Bovine Foetus - Shivaraj (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted on isolation and confirmation of leptospira canicola from the aborted bovine foetus. Out of the 24 aborted bovine samples subjected for isolation, one sample has yielded the growth after two weeks of inoculation. The conventional polymerase chain reaction (PCR) using G1G2 and LipL32 primers have shown the amplicon size of 285 bp and 756 bp respectively. The positive PCR sample/isolate was confirmed as serogroup canicola by subjecting it to “O” gene specific cluster multiplex PCR with an amplicon size of 341bp.
Keywords: Leptospira canicola; Leptospirosis; Lip L32; Multiplex PCR